Toxicity of insecticides used in rice crop on the egg parasitoid Trichogramma pretiosum (Hymenoptera: Trichogrammatidae) under field conditions - Rakes, Matheus; Pasini, Rafael Antonio; Morais, Maira Chagas; Araujo, Mikael Bolke; Malaquias, Jose Bruno [UNESP]; Bernardi, Daniel; Grutzmacher, Anderson Dionei (Univ Federal Santa Maria, 2023)
We evaluated under field conditions the toxicity of insecticides previously identified as harmful in laboratory and semifield bioassays on the parasitoid Trichogramma pretiosum (Hymenoptera: Trichogrammatidae). The experiments were conducted during the 2019/20 and 2020/21 harvests in rice fields. Following the recommendations of the International Organization for Biological and Integrated Control (IOBC), four insecticides were applied in 64 m2 experimental plots. Subsequently, T. pretiosum was released inundatively. To verify parasitism rates, at 1, 2, 4 and 6 days after release (DAR) of the parasitoids, eggs from the host Ephestia kuehniella (Lepidoptera: Pyralidae) were offered. After determining the number of parasitized eggs, the data were grouped into a reduction coefficient (Ex) to provide a single result for the effects of the insecticides on parasitoid. For both the 2019/20 and 2020/21 evaluated crops, it was found that at 2 DAR, the highest parasitism rates occurred. In contrast, in 6 DAR, no parasitism rates were observed. Lambda-cyhalothrin, thiamethoxam, and zeta-cypermethrin were classified as moderately harmful; thiamethoxam + lambda-cyhalothrin was classified as harmful. Following IOBC guidelines, the toxicity of these products under field conditions is lower than that obtained in the laboratory or semi-field for the T. pretiosum. However, these insecticides should be avoided, or used at times that do not coincide with the release or presence of the parasitoid in the field.
Keywords: biological control; chemical control; integrated pest management; natural enemies; pesticide selectivity